Design of a miniaturized patch antenna for 2.45/5.8 GHz applications - Laabadli, Abdel-Ali; Mejdoub, Youssef; Elamri, Abdelkebir; Tarbouch, Mohamed (Institute of Advanced Engineering and Science, 2025)
A miniaturized antenna for 2.45 and 5.8 GHz applications is presented in this paper. The designed antenna is based on two metamaterial unit cells which resonate at 2.45 and 5.8 GHz. They are etched on the ground plane of the conventional patch antenna that resonates at 3.38 GHz. The substrate and metal chosen in this design are respectively, Epoxy FR-4 (with permittivity 4.4, loss tangent of 0.025, and thickness of 1.6 mm) and copper annulled. The simulation of the antenna was done with a CST solver. The proposed miniaturized antenna has two main bands: the inferior band 2.45 GHz and the superior band 5.8 GHz. On the inferior band, the gain and bandwidth are 1.39 dB and 76.4 MHz, and on the superior band, they are 2.05 dB and 160 MHz.